The Disjoint Between Stakeholders' and Voters' Positions on the Political Economy of Energy Policy - Kankanam Pathiranage, Heshan Sameera (Business and Economic Research, 2022)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">The formulation of policies on renewable energy is susceptible to conflicts of interest, which may paralyze the efficiency of the policies in driving sustainable development. A meta-analysis study was adopted to comprehensively explore the interplay between public interests and stakeholders' perceptions in the energy sector. Twenty-three studies will be selected following rigorous inclusion and exclusion criteria. The extracted data were also analyzed using HOMA and MARA. The study elucidated that the public is sensitive to procedural justice, distribution justice, placement, and trust. Conversely, stakeholders are devoted to ensuring energy autonomy and embracing renewable energy as a solution to the climatic issues associated with fossil fuels. If the interests of the two parties are harmonized, feasible policies that will be deemed acceptable by the public will be formulated.